Special Issue "Oxidative Stress in Aging and Associated Chronic Diseases" - Cristina Mas-Bargues; Matilde Alique; Mª Teresa Barrús-Ortiz; Consuelo Borrás; Raquel Rodrigues-Díez (MDPI AG, 2022)
Aging is a risk factor for several diseases, including cardiovascular disease, type 2 diabetes, hypertension, cancer, osteoarthritis, and Alzheimer; oxidative stress is a key player in the development and progression of aging and age-associated diseases [...]